L’estructura prosòdica i l’accent - Serra, Pep (Caplletra. Revista Internacional de Filologia, 1995)
The internal structure of syllables has proved to be crucial in the definition of the basic lexical stress system. In the assignment of stress to word entries, Catalan behaves as a quantity-sensitive language: syllable moras are the basis in computation. Two major patterns have been observed at the surface level: (a) Vowel-final words have penultimate stress, (b) Consonant-final words have final stress. The analysis has benefited from the recognition that morphemes, not words, are the proper domain of stress algorithms. The final stress of words ending in a vowel, as in camió or català, conforms to the regular pattern mentioned above, since the underlying form of the last morpheme ends in a consonant. Most exceptions have shown to he only apparent, although special devices are required to account for some cases. Optimality theory has been used to provide a coherent explanation of both exceptions and regular patterns.